Mengembangkan Basic Kecerdasan Spiritual melalui Religious Culture di Sekolah Vokasi - Surawan; Sarifah, Siti; Dyah Apriliani, Anita (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
This research departs from the importance of increasing spiritual intelligence through the application of religious culture in schools. The purpose of this study was to determine the application of religious culture in increasing the spiritual intelligence of students at SMK Negeri 1 Sampit. This study uses a qualitative method that produces descriptive data. The subjects in this study were students of SMK Negeri 1 Sampit totaling 7 people and the informants were 2 teachers of Islamic Religious Education, 1 homeroom teacher, and the principal. The results of this study indicate that the application of religious culture at SMK Negeri 1 Sampit, namely (a) 3S (Smile, Greet, Greeting) can be realized by saying